HTLV-1 propels thymic human T cell development in "human immune system" Rag2⁻/⁻ gamma c⁻/⁻ mice. - Julien Villaudy (Public Library of Science (PLoS), 2011)
Alteration of early haematopoietic development is thought to be responsible for the onset of immature leukemias and lymphomas. We have previously demonstrated that Tax(HTLV-1) interferes with ß-selection, an important checkpoint of early thymopoiesis, indicating that human T-cell leukemia virus type 1 (HTLV-1) infection has the potential to perturb thymic human αβ T-cell development. To verify that inference and to clarify the impact of HTLV-1 infection on human T-cell development, we investigated the in vivo effects of HTLV-1 infection in a "Human Immune System" (HIS) Rag2⁻/⁻γ(c)⁻/⁻ mouse model. These mice were infected with HTLV-1, at a time when the three main subpopulations of human thymocytes have been detected. In all but two inoculated mice, the HTLV-1 provirus was found integrated in thymocytes; the proviral load increased with the length of the infection period. In the HTLV-1-infected mice we observed alterations in human T-cell development, the extent of which correlated with the proviral load. Thus, in the thymus of HTLV-1-infected HIS Rag2⁻/⁻γc⁻/⁻ mice, mature single-positive (SP) CD4⁺ and CD8⁺ cells were most numerous, at the expense of immature and double-positive (DP) thymocytes. These SP cells also accumulated in the spleen. Human lymphocytes from thymus and spleen were activated, as shown by the expression of CD25: this activation was correlated with the presence of tax mRNA and with increased expression of NF-kB dependent genes such as bfl-1, an anti-apoptotic gene, in thymocytes. Finally, hepato-splenomegaly, lymphadenopathy and lymphoma/thymoma, in which Tax was detected, were observed in HTLV-1-infected mice, several months after HTLV-1 infection. These results demonstrate the potential of the HIS Rag2⁻/⁻γ(c)⁻/⁻ animal model to elucidate the initial steps of the leukemogenic process induced by HTLV-1.